Sosok Guru Ideal dalam Puisi-Puisi Karya M. Faizi: Studi Linguistik Sosiokognitif - Baehaqie, Imam; Sumartini, Sumartini; Utomo, Asep Purwo Yudi; Nugroho, Muhammad Irsyad Hamid; Rahmat, Arzha Ali (Balai Bahasa Sulawesi Selatan, 2025)
The purpose of this study is to describe the figure of the ideal teacher represented in the poetry collection Jalan Empat by M. Faizi. The data collection method in this study is the listening method, namely listening to the use of language contained in the poem. The data analysis method applied in this study is the referential matching method. In this case, the determinant is the reality indicated by the language contained in the poem by utilizing Van Dijk's critical discourse analysis model. Through poetry, the poet, in this case M. Faizi, voices all things, including quality education. Quality education should be supported by the excellence of all its components, including the figure of the teacher. In the poetry collection Jalan Empat, there are poems that represent the subject of teachers. The poems in question are the poems Kularutkan Anxiety Kularutkan Harapan, Wafat Kiai, and Ode Guru. From the analysis of these poems, it can be seen that the characteristics of an ideal teacher, according to M. Faizi, include being able to recognize and guide students' emotions, maintaining children's happiness, working out of a calling and sincerity, and being able to develop students' cognitive, psychomotor, and affective intelligence. AbstrakTujuan penelitian ini ialah mendeskripsikan sosok guru ideal yang direpresentasikan dalam kumpulan puisi Jalan Keempat karya M. Faizi. Metode pengumpulan data dalam penelitian ini adalah metode simak, yakni menyimak penggunaan bahasa yang terdapat dalam puisi. Adapun metode analisis data yang diterapkan dalam penelitian ini ialah metode padan referensial. Dalam hal ini, penentunya ialah kenyataan yang ditunjuk bahasa yang terdapat dalam puisi dengan memanfaatkan analisis wacana kritis model Van Dijk. Lewat puisi penyair dalam hal ini M. Faizi menyuarakan banyak hal, termasuk di antaranya pendidikan yang berkualitas. Pendidikan yang bermutu hendaknya didukung oleh adanya keunggulan semua komponennya, tak terkecuali sosok guru. Dalam kumpulan puisi Jalan Keempat dapat ditemukan adanya puisi-puisi yang merepresentasi perihal guru. Puisi-puisi yang dimaksudkan adalah puisi Kularutkan Cemas Kularutkan Harap, Wafat Kiai, dan Ode Guru. Dari analisis terhadap sejumlah puisi tersebut dapat diketahui bahwa karakter sosok guru ideal dalam pandangan M. Faizi antara lain ialah mampu mengenali emosi murid dan membimbingnya, menjaga keceriaan anak, bekerja karena panggilan jiwa dan ketulusan, serta mampu mengembangkan kecerdasan kognitif, psikomotorik, dan afektif siswa.